Menjadi Guru Profesional di Abad 21: Keterampilan Dalam Literasi Digital - ., Munawir; Muhidin, Nur Muhammad (Universitas Veteran Bangun Nusantara, 2025)
: In the 21st century, the role of teachers has significantly evolved, driven by rapid technological advancements and the dynamic needs of modern learners. Today’s professional teachers must possess a wide range of competencies to stay relevant and effective. Among the essential skills are innovative pedagogical strategies, technological literacy, and strong social-emotional abilities. The integration of digital tools in education is no longer optional but a necessity to foster student engagement and personalized learning. Furthermore, teachers must develop positive relationships with students to create inclusive and supportive learning environments. Continuous professional development is also crucial, as it allows educators to adapt to curriculum changes, educational policies, and emerging global trends. The ability to reflect on one’s practice, embrace feedback, and collaborate with peers contributes to a teacher's overall growth and professionalism. Inconclusion, the 21st-century teacher is not merely a transmitter of knowledge but a facilitator, mentor, and lifelong learner who is equipped to meet the challenges of modern education. Mastery of these skills ensures that teachers remain impactful and relevant in guiding the next generation